Н. КУКОЛЬНИК ОБ УКРАИНСКОМ ЯЗЫКЕ (Zaporizhzhia Historical Review, 2021)
The report is devoted to product of Russian writer Nestora of the Puppeteer « the Azov sitting ». It is considered(examined) as the writer who has negatively responded about "Кобзаре" Shevchenko, transfers informal conversation of characters in the Ukrainian language. One Ukrainian song which is sung in a course of action by one of heroes of a drama understands, and is shown, that the author is not realized, involuntarily, in обмолвках, revolutions and other receptions as though blabs out in the love to Ukrainian people and its language. Review Чернышевского « the Azov sitting » which reproaches the Puppeteer with unwillingness to use « correct малорусский language » is considered also. As has shown the analysis дневниковой (not published till now) N.Kukol'nika's records, he invited to debate on destiny of Ukraine so imperial authority did not recognize Ukrainian people for the nation.